CLDN8, an androgen‐regulated gene, promotes prostate cancer cell proliferation and migration. Issue 7 (2nd June 2017) - Ashikari, Daisaku; Takayama, Ken‐ichi; Obinata, Daisuke; Takahashi, Satoru; Inoue, Satoshi
Abstract : The proliferation of prostate cancer cells is controlled by the androgen receptor (AR) signaling pathway. However, the function of AR target genes has not been fully elucidated. In previous studies, we have identified global AR binding sites and AR target genes in prostate cancer cells. Here, we focused on Claudin 8 (CLDN8), a protein constituting tight junctions in cell membranes. We found one AR binding site in the promoter region and two functional androgen‐responsive elements in the sequence. Reporter assay revealed that transcriptional activation of the CLDN8 promoter by androgen is dependent on these androgen‐responsive elements. Furthermore, CLDN8 mRNA is induced by androgen time‐dependently and the induction is blocked by AR inhibitor, suggesting that AR is involved in the transcriptional activation. In addition, our functional analyses by overexpression and knockdown of CLDN8 mRNA indicate that CLDN8 promotes prostate cancer cell proliferation and migration. Claudin 8 was overexpressed in prostate cancer clinical samples compared to benign tissues. Furthermore, we found that CLDN8 regulates intracellular signal transduction and stabilizes the cytoskeleton. Taken together, these results indicate that CLDN8 functions as an AR downstream signal to facilitate the progression of prostate cancer. Claudin 8 may be a novel molecular target for prostate cancer therapy. Abstract : CLDN8 is identified as an androgen‐receptor regulated gene in prostate cancer and promotes cell proliferation and migration.